2006
DOI: 10.1111/j.1469-7998.2006.00252.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of cobras from southern Africa

Abstract: Large slender-bodied snakes that forage actively for a generalized array of small vertebrates are conspicuous elements of the terrestrial snake fauna of most continents; the venomous elapid species fill this role in much of Asia, Africa and Australia. Our dissections of eight species of cobras from southern Africa Aspidelaps, Hemachatus, Naja; Serpentes and Elapidae (total of 1290 specimens) provide extensive data on sexual dimorphism, reproductive biology and food habits. Females grow larger than males in Asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
44
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 47 publications
5
44
3
Order By: Relevance
“…Discrepancies between our findings and those of Shine et al. () likely arise as a result of differences in sampling effort and the number of methods employed: method‐specific biases in the detection of different prey items in animal diets can severely limit studies of prey diversity when only one method is used (Glaudas et al. ).…”
contrasting
confidence: 74%
See 3 more Smart Citations
“…Discrepancies between our findings and those of Shine et al. () likely arise as a result of differences in sampling effort and the number of methods employed: method‐specific biases in the detection of different prey items in animal diets can severely limit studies of prey diversity when only one method is used (Glaudas et al. ).…”
contrasting
confidence: 74%
“…This result was somewhat surprising given that Shine et al. (), in an excellent empirical review of southern African cobra diets, found no evidence of ophiophagy in N . nivea or N. subfulva whereas our assessment suggests snakes account for about 32% and 24% of their diets, respectively.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…We focused on two species of venomous snakes that prey on rodents and live sympatrically with X. inauris, the puff adder (Bitis arietans) and the snouted cobra (Naja annulifera) (Broadley, 1990;Phelps, 1989;Shine et al, 2007). The venom of B. Arietans causes severe local and systemic effects to tissue including swelling, haemorrhage, and necrosis (Rippey et al, 1976;Warrell et al, 1975;Mallow et al, 2003).…”
mentioning
confidence: 99%